2019
DOI: 10.20414/betajtm.v12i1.264
|View full text |Cite
|
Sign up to set email alerts
|

Culture and mathematics learning: Identifying students’ mathematics connection

Abstract: Abstrak: Koneksi matematika mendukung siswa menemukan berbagai kemungkinan strategi dalam penyelesaian masalah. Produk budaya memungkinkan dapat dijadikan objek matematika dalam pembelajaran. Artikel ini merupakan bagian dari penelitian yang merancang desain pembelajaran berbasis budaya lokal yang bertujuan mengidentifikasi kemampuan koneksi matematika siswa. Data dikumpulkan melalui tes yang diberikan kepada 341 siswa dan wawancara tidak terstruktur terhadap 9 siswa yang dipilih berdasarkan penyelesaian tes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Existing mathematics education research is generally more focused on the classroom. However, there are new findings that show that a lot of mathematics knowledge can also be obtained outside of school, one of them is findings about ethnomathematics [14]. Students develop representations and procedures into their cognitive system, which is a process that occurs in the context of social activities that are built.…”
Section: Methodsmentioning
confidence: 99%
“…Existing mathematics education research is generally more focused on the classroom. However, there are new findings that show that a lot of mathematics knowledge can also be obtained outside of school, one of them is findings about ethnomathematics [14]. Students develop representations and procedures into their cognitive system, which is a process that occurs in the context of social activities that are built.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies link culture and mathematics learning (e.g., Kusaeri, Pardi, & Quddus, 2019;Susanti et al, 2020). The studies found that mathematics learning associated with local culture supported students' understanding of mathematical concepts even though the cultural products were just used as the learning media.…”
Section: A Introductionmentioning
confidence: 99%